PENGARUH PENGETAHUAN ZAKAT,TINGKAT PENDAPATAN, TINGKAT KEIMANAN, KEPERCAYAAN TERHADAP MOTIVASI PETANI SAWIT DALAM MEMBAYAR ZAKAT HASIL PERKEBUNAN (STUDI KASUS PETANI DI KABUPATEN BENGKALIS-RIAU) - Nanda Suryadi; Rimet Rimet (Universitas Lancang Kuning, 2023)
The purpose of this study was to determine the effect of knowledge of zakat, income level, level of faith, trust in the motivation of oil palm farmers in paying zakat from plantation yields (Case Study of Farmers in Bengkalis-Riau Regency). This research was conducted in Bengkalis Regency. This research uses the Structure Equation Model (SEM) Smart Pls by analyzing the facts that have occurred. In this study, primary data were collected using a questionnaire with the Slovin sampling method totaling 99. Respondents in this study were oil palm farmers in Bengkalis Regency. This study produced interesting findings, including knowledge of zakat has a significant effect on motivation to pay zakat, income level has a significant effect on motivation to pay zakat Keywords Zakat Knowledge, Income Level, Faith Level, Trust, Motivation